Transition between Open and Guided Inquiry Instruction - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
Scientific inquiry refers to activities in which knowledge and understanding of how scientists study the natural world. Depending on how much teacher structure is supplied and whether there is an already existing solution to the problem or question, inquiry was classified as confirmation, structured, guided and open inquiry. The research aims at presenting the instance of transition between guided and open inquiry. This study was carried out with 25 pre-service teachers at a state university. Two activities were practiced. During the activities, pre-service teachers designed their own experiments, made researches about their concepts and made argumentation about experiments. When applying open inquiry appeared difficulty, guided inquiry was applied. These difficulties were 1) Absence of science process skills as formulating hypotheses, research questions and defining variables. 2) Pre-service teachers met for the first time with an inquiry based laboratory. 3) When researching about concepts and associating their experiments with works of scientists, they did not know where and how to start research. (C) 2014 The Authors. Published by Elsevier Ltd. Open access under CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/).
Keywords: Open inquiry; guided inquiry; physics education; pre-service teachers; SCIENCE; STUDENTS